The syndrome ebook A kingdom keepers adventure. - Pearson, Ridley (The Kingdom Keepers., 2015)
When Amanda travels east to Orlando on a hunch, she's met with the worst news possible. Kingdom Keeper Finn Whitman is missing. Calling on her own gift (she's telekinetic), her sister Jess's ability to dream the future, and their fellow Fairlie Mattie Weaver's unexplained ability to read minds through physical contact, the three gifted girls must navigate treachery, deception, and the stubborn, unwilling parents of the missing Keepers if they're to save their friends.